Peningkatan Kualitas dan Kemampuan Pelayanan Praktikum Mikrobiologi Bagi Guru SMA di Kota Jayapua - Lantang, Daniel; Rampa, Ester; Menufandu, Herlina; Allo, Elisabeth Payung; Sinaga, Herlando (Bakti Hayati: Jurnal Pengabdian Indonesia, 2023)
Along with the advancement of science in the health sector, biology teachers in high school must understand microbiology, especially have the ability to provide practicum to students so that students have the ability in the field of microbiology. The low understanding of students about microbiology subjects is due to the absence of microbiology practicum in high school. This service is carried out by giving a pre test, skills training and mentoring to teachers so that their knowledge increases. From the results of the service, it is known that knowledge and skills of the teachers increased and already understood and understood the microbiology practicum instruments.